Brucella-Induced Downregulation of lncRNA Gm28309 Triggers Macrophages Inflammatory Response Through the miR-3068-5p/NF-κB Pathway - Deng, Xingmei; Guo, Jia; Sun, Zhihua; Liu, Laizhen; Zhao, Tianyi; Li, Jia; Tang, Guochao; Zhang, Hai; Wang, Wenjing; Cao, Shuzhu; Zhu, Dexin; Tao, Tingting; et al. (Frontiers in Immunology, 2020)
ABSTRACT Objectives: The underlying mechanism of the inflammatory response against Brucellosis caused by Brucella remains poorly understood. This study aimed to determine the role of long non-coding RNAs (lncRNAs) in regulating of inflammatory and anti-Brucella responses. Materials and methods: Microarray analysis was performed to detect differentially expressed lncRNAs in THP-1 cells infected with an S2308 Brucella strain. The candidate lncRNAs were screened using bioinformatic analysis and siRNAs; bioinformatic prediction and luciferase reporter assay were also conducted, while inflammatory responses was assessed using RT‐qPCR, western blot, immunofluorescence, ELISA, HE and immunohistochemistry. Results: The lncRNA Gm28309 was identified to be involved in regulating inflammation induced by Brucella. Gm28309, localized in the cytoplasm, was down-expressed in RAW264.7 cells infected with S2308. Overexpression of Gm28309 or inhibition of miR-3068-5p repressed p65 phosphorylation and reduced NLRP3 inflammasome as well as IL-1β and IL-18 secretion. Mechanistically, Gm28309 acted as a ceRNA of miR-3068-5p to activate NF-κB pathway by targeting κB-Ras2, an inhibitor of NF-κB signaling. Moreover, the number of intracellular Brucella was higher when Gm28309 was overexpressed or when miR-3068-5p or p65 was inhibited. However, these effects were reversed by the miR-3068-5p mimic. Conclusions: Our study demonstrates, for the first time, that LncRNAs are involved in regulating immune responses during Brucella infection, and Gm28309, an lncRNA, plays a crucial role in activating NF-κB/NLRP3 inflammasome signaling pathway.